Use of a Baculovirus-Expressed Structural Protein for the Detection of Antibodies to Foot-and-Mouth Disease Virus Type A by a Blocking Enzyme-Linked Immunosorbent Assay - Ko, Young-Joon (American Society for Microbiology (ASM), 2010)
A blocking enzyme-linked immunosorbent assay (ELISA) with a baculovirus-expressed structural protein was developed for the detection of antibodies to foot-and-mouth disease virus type A. It exhibited 99% specificity with a cutoff of 53% inhibition. Its sensitivity was comparable to the sensitivities of the virus neutralization test and the liquid-phase blocking ELISA, indicating its potential as an alternative assay.